SEASONAL DYNAMICS OF ENSO IMPACT ON SEA SURFACE TEMPERATURE VULNERABILITY IN THE MADURA STRAIT COAST, INDONESIA - Widagdo, Supriyatno; Semedi, Bambang; Firdaus, Muhamad (Journal of Environmental Engineering and Sustainable Technology, 2025)
The El Niño-Southern Oscillation (ENSO) is a dominant climate phenomenon affecting the global oceanographic system; however, understanding of the seasonal variability of its impact on semi-enclosed waters, such as the Madura Strait, remains limited. This knowledge gap is crucial because the Madura Strait has complex bathymetric characteristics and is a strategic area for coastal economic activity in Indonesia. This study aimed to analyze the seasonal dynamics of ENSO's influence on coastal vulnerability in the Madura Strait. The study used secondary CMEMS data for sea surface temperature, salinity, and chlorophyll-a for the period 2019-2024, covering neutral, El Niño, and La Niña phases. The analysis was conducted using Ocean Data View spatial visualization, descriptive statistics, and hierarchical cluster analysis, dividing the region into three geographic zones: western, central, and eastern. ENSO exhibits a varying seasonal influence with a bimodal pattern correlated with the monsoon cycle. Sampang emerged as a vulnerability hotspot with an extreme anomaly of -1.4°C. The western zone exhibits high resistance, the central zone is most responsive, and the eastern zone is highly vulnerable. El Niño dominated the three seasons, whereas La Niña dominated the early transitional season. The coastal vulnerability of the Madura Strait to ENSO is spatially and temporally heterogeneous, with distinct zoning. These findings provide a scientific basis for zoning-based adaptation strategies and early warning systems in Indonesia's strategic coastal areas.Keywords: ENSO, seasonal variability, coastal vulnerability, Madura Strait